Ibuisme negara : Konstruksi sosial keperempuanan orde baru / Julia Suryakusuma; Penyunting, Uswatul Chabibah dan Julia Suryakusuma; Penerjemah, Nugraha Katjasungkana, Tam Notosusanto dan Julia Suryakusuma - JULIA Suryakusuma; NUGRAHA Katjasungkana; TAM Notosusanto; USWATUL Chabibah (Komunitas Bambu, 2011)
xxx, 162 hlm. ; 21 cm.